Comparison Of Academic Achievement For Course Practice Before Pandemic Vs During Pandemic - Ladjar, Maria Andriani Barek; Babang, Veramyta Maria Martha Flora (UNIB Press, 2022)
The research objective was to compare the academic achievement of practical courses before the pandemic period and after the pandemic period as a consideration for researchers to modify distance learning which is currently still ongoing. The research carried out included the type of Quasi-Experimental Designs using the Nonequivalent Comparison Group Design. The practical subjects studied were Pencak Silat and Volleyball Learning before the pandemic and during the pandemic. Data collection for Pencak Silat group and the Volleyball Group before and during the Pandemic Period, from academic achievements scores for the Mid-Semester Examination and the Final Semester Examination. The group before the pandemic, all assessments of the Midterm Examination and the End of Semester Examination practiced directly in front of the Lecturer, while for the group during the pandemic, students recorded and uploaded to Youtube, then the video link sent to E-learning to be assessed by the Lecturer. Group Pencak Silat and Volleyball before pandemic, there are students of class 2018, while group Pencak Silat and Volleyball during pandemic, there area students of class 2020. Group Pencak Silat before pandemic 20 students, Group Pencak Silat during pandemic 20 students, group Volleyball before pandemic 20 students, and group Volleyball during pandemic 20 students. So, total 80 students were sampled in this research. Based on the results of statistical tests using SPPS with the Independent Sample T-Test, the Sig. (2-tailed) 0.011 <0.025, so Ho is rejected, so H1 is accepted. In other words, there is a significant difference between the academic achievement of the Pencak Silat Subject before and during the Pandemic Period. Based on the results of statistical tests using SPPS with the Independent Sample T-Test, the Sig. (2-tailed) of 0.000 <0.025 then Ho is rejected so that H1 is accepted. In other words, there is a significant difference between the academic achievement of volleyball learning subjects before and during the pandemic. The group that took the Pencak Silat Course before the pandemic and during the pandemic showed pre-test data for the group's Mean Value before the pandemic of 73.75 > 66.75 during the pandemic, and post-test data for the group's Mean Value before the pandemic of 77.80 > 69.80 during the pandemic, thus showing The mean value of the group before the pandemic was higher than the group during pandemic for students who took the Pencak Silat Course. The group that took the Volleyball Learning Course before the pandemic and during the pandemic showed pre-test data for the group's Mean Value before the pandemic of 70.75 > 64.05 during the pandemic, and post-test data for the group's Mean Value before the pandemic of 78.25 > 68.35 during the pandemic, so that shows the Mean value of the group before the pandemic was higher than the group during the pandemic for students who took the Volleyball Learning Course. The conclusion drawn from the description of the data above, shows the difference in the average value where the group before the pandemic has a higher average than during pandemic. Lecturers need to find solutions so that through online lectures students' academic achievement remains the same as academic achievement during face-to-face lectures.